Jealousy, Femininity and Desire A Lacanian Reading - Tor-Zilberstein, Dana. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
Drawing on Freudian and Lacanian psychoanalysis, this book intervenes into debates concerning the relation between jealousy and envy on the one hand, and sexual difference on the other. The author presents an original distinction between what is termed "feminine" and "phallic" forms of jealousy while mapping and theorizing other types of jealousy that she finds in the writings of Sigmund Freud and Jacques Lacan. The discussion performs literary-critical readings of texts by Olivia Shakespear and Marguerite Duras as a means of shedding light on the topic and the distinction. Further, it discusses the challenge posed by jealousy's particular mode of jouissance and its possible vicissitudes. Though the experience of jealousy can be ravaging, the author claims, it also provides the subject an opportunity to reorient its relation to jouissance and thereby experience significant psychical change. In doing so, it provides a new outlook on jealousy as being connected to both femininity and desire, unveiling its complex character, features, and vitality within a Lacanian psychoanalytic framework. It will appeal in particular to those with an interest in psychoanalysis, literary theory and critical theory. Dana Tor-Zilberstein Dana Tor-Zilberstein practices psychoanalysis in Tel Aviv, Israel. She is a postgraduate of the department of English at Tel-Aviv University, where she also graduated in Law. She is a member of the editorial team of "Et Lacan" magazine published by the Giep-NLS, the Israeli group of the New Lacanian School. She is a translator in the psychoanalytic field. Her authored publications in English include 'The Oresteia' and the Act of Revenge: of Desire and Jouissance (2022).
1 Introduction -- 2 What Is Jealousy? Jealousy and Envy from Aristotle to Today -- 3 Drive Jealousies in the Development of the Subject -- 4 Two Instances of Jealousy inBeauty's Hourand in the Mirror Stage -- 5 Two Types of Jealousy-Phallic Jealousy and Feminine Jealousy -- 6 Jealousy and Identification-Dora and the Young Homosexual Woman -- 7 Jealousy Among Men: Schreber's Delusional Jealousy and Little Hans' Feminine Jealousy -- 8 Ravissement and Jealousy Without Pain -- 9 The Lover: The Writing of Feminine Jealousy.
Keywords: Psychoanalysis; Literature -- Philosophy; Critical theory; Culture -- Study and teaching; Psychoanalysis; Literary Theory; Critical Theory; Cultural Theory